Metabolism and Innate Immunity Meet at the Mitochondria - Bahat, Amir; MacVicar, Thomas; Langer, Thomas (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are master regulators of metabolism and have emerged as key signalling organelles of the innate immune system. Each mitochondrion harbours potent agonists of inflammation, including mitochondrial DNA (mtDNA), which are normally shielded from the rest of the cell and extracellular environment and therefore do not elicit detrimental inflammatory cascades. Mitochondrial damage and dysfunction can lead to the cytosolic and extracellular exposure of mtDNA, which triggers inflammation in a number of diseases including autoimmune neurodegenerative disorders. However, recent research has revealed that the extra-mitochondrial exposure of mtDNA is not solely a negative consequence of mitochondrial damage and pointed to an active role of mitochondria in innate immunity. Metabolic cues including nucleotide imbalance can stimulate the release of mtDNA from mitochondria in order to drive a type I interferon response. Moreover, important effectors of the innate immune response to pathogen infection, such as the mitochondrial antiviral signalling protein (MAVS), are located at the mitochondrial surface and modulated by the cellular metabolic status and mitochondrial dynamics. In this review, we explore how and why metabolism and innate immunity converge at the mitochondria and describe how mitochondria orchestrate innate immune signalling pathways in different metabolic scenarios. Understanding how cellular metabolism and metabolic programming of mitochondria are translated into innate immune responses bears relevance to a broad range of human diseases including cancer.